2020
DOI: 10.1101/2020.01.14.903849
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of phosphorylation on thermal stability of proteins

Abstract: Reversible protein phosphorylation regulates virtually every cellular process and is arguably the most wellstudied post-translational modification. Still, less than 3% of the phosphorylation sites identified in humans have annotated functions. Functionally-relevant phosphorylation sites are known to trigger conformational changes to proteins and/or to regulate their interactions with other proteins, nucleic acids and small molecules -all of which can be reflected in the thermal stability of a protein. Thus, co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 32 publications
2
39
1
Order By: Relevance
“…In contrast to the Huang et al dataset, we find that the stability of phosphopeptides correlates well with the stability of their respective proteins (R 2 =0.79 for mean R s comparisons) ( Fig. 1d), suggesting that most phosphosites do not alter protein stability as also observed by Potel et al 3 . As expected, the stability of non-modified peptides present in the phosphopeptide-enriched samples also correlated well with their proteins (R 2 = 0.90 for mean R s comparisons), indicating that R s measurements in the phosphopeptide samples and protein samples can be reliably compared ( Supplementary Fig.…”
contrasting
confidence: 70%
See 1 more Smart Citation
“…In contrast to the Huang et al dataset, we find that the stability of phosphopeptides correlates well with the stability of their respective proteins (R 2 =0.79 for mean R s comparisons) ( Fig. 1d), suggesting that most phosphosites do not alter protein stability as also observed by Potel et al 3 . As expected, the stability of non-modified peptides present in the phosphopeptide-enriched samples also correlated well with their proteins (R 2 = 0.90 for mean R s comparisons), indicating that R s measurements in the phosphopeptide samples and protein samples can be reliably compared ( Supplementary Fig.…”
contrasting
confidence: 70%
“…To minimize technical noise derived from sample preparation, peptide samples should be labeled and mixed prior to phosphopeptide enrichment (Supplementary Discussion and accompanying manuscript 3 ). Because scaling-up isobaric chemical labeling increases reagent costs substantially, we have developed an alternative approach to identify phosphosites that alter thermal stability, that we call Dali (Fig.…”
mentioning
confidence: 99%
“…Finally, we were able to evaluate the hits from our study in comparison to two previous thermal protein profiling (TPP) studies performed in human cells 19,20 . When looking at the functional score distributions, all three studies were observed to be enriched for functional phosphoproteins ( Supp Fig 2a ).…”
Section: Comparison Of Experimental Functional Phosphorylation Studiesmentioning
confidence: 99%
“…Experimental approaches for high-throughput identification of protein phosphosite functions have been largely lacking. More recently, a promising approach has been to use a modified thermal proteome profiling (TPP) approach where the TPP protocol is conducted in conjunction with phosphoproteomics to identify functional phosphosites [18][19][20][21] . This method has proven useful to directly determine whether a phosphosite is likely to be functional or not.…”
Section: Introductionmentioning
confidence: 99%
“…Many physiological changes to the functional state of a protein are re ected in altered protein thermostability 8,9 . Thermal proteome pro ling (TPP) measures protein thermal stability in situ on a proteome-wide scale and is a powerful tool for identifying proteins with altered biophysical states in living cells: protein-protein interactions (PPIs), the reorganization of protein complexes 10,11 , posttranslational modi cations 12,13 , or the interaction of proteins with co-factors, small molecules, or nucleic acids 14 . The method quanti es protein abundance changes in the same samples, offering a comprehensive insight into the physiological changes that occur during cellular perturbations.…”
Section: Introductionmentioning
confidence: 99%